Analysis of the Turkish 2001 Constitutional Amendments in the Context of Fundamental Rights and Freedoms from the Perspective of European Rule of Law - Tunç, Bilal; Yildirim, Sefa (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
Türkiye’s current constitution, the 1982 Constitution, is modelled on the constitutions of European states. In fact, the 6th amendments to the 1982 Constitution, which is the subject of this study, was made on October 3, 2001 within the framework of harmonization with the European Union acquis. With this regulation, in addition to the initial text of the Constitution, several articles[1] were amended. The main purpose of making these amendments was to make the 1982 Constitution harmonized within the scope of the accession works to the European Union. The aim of this study was to reveal the contribution of Articles 13, 14, 19, 20, 21, 22, 23, 26, 28, 31, 33, 34, 36, 38 and 40, regulating the issues in the context of protecting fundamental rights and freedoms and amended in 2001, to the development of fundamental rights and freedoms in Türkiye. For this purpose, it was aimed to reveal in detail the effect of the said Constitutional amendment on the development of human rights and freedoms. This study was created by making use of the Official Gazette and copyrighted works through a qualitative study in which the document analysis techniques were used in order to show how Türkiye embarked on the path of European legal development by ensuring constitutional fundamental rights.